Special Rules for the Church: The “Ministerial” Exception under the Americans with Disabilities Act - Taylor, Robin M. (Dialog, 2012)
In the Hosanna-Tabor case, the United States Supreme Court held that there is a broad exception under the Americans with Disabilities Act (ADA) for employees who are ministers. A Lutheran Church–Missouri Synod school could fire an elementary school teacher with a disability because she was a “called teacher,” even though the termination would otherwise have violated the ADA. The Evangelical Lutheran Church in America supported this decision, but this contradicts the ELCA's position with respect to persons living with disabilities. It also reflects an “idolatry of the call” inconsistent with the priesthood of all believers. A better course for the ELCA is to agree to be bound by those standards that it advocates for the secular world.